(untitled) (Journal of Academic Research, 2024)
As the automation system has advanced, there has been a wave of concern that lab automation will replace technicians. This paper aims to investigate the current impact of automation on the number of laboratory technicians, with special consideration given to knowing the current level of automation in the chemistry and hematology laboratories in both sectors. Four months of data collection using field visits and postal questionnaires that included demographics of laboratory technicians and types of automated analysis systems. Fully automated analyzers were positively associated with the number of technicians in the chemistry departments of the private sector (P = 0.03). However, the strategy adopted by the two sectors, which was based on not introducing pre- and post-analysis automation systems, contributed to its lack of impact on the laboratory workforce. Thus, manual labor is not dispensed with in all laboratories, allowing for multiple job roles for the laboratory workforce.